Nowe technologicznie realizacje telewizyjne i ich walory edukacyjne - Michałowski, Marian (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
The technological development and its influence on the whole social life in multiform way leads to necessity of exploring problems connected with electronic audio-visual transmission, characterised by migration from analog technology to digital pictures generated by computers; in other words from technical reproduction to computer simulation (many times much more attractive than real life and world). Actually digital technology extorts changes and there is necessary to recognise its features and consequences - the potential chances and threats of electronic images are the challenges for present science, especially in the humanistic area. The main problem is the lack of insufficient theory for performing science researches in methodologically proper way. Television and its programme streams create educational space for the spectators and therefore it seems reasonable to examine the usefulness of TV productions (with participation of new technology) what allows to enrich theory, to elaborate principles for practice and probably to qualify further proper development.
New technological television productions and their educational values